PERANCANGAN GAME PARKOUR 3D BESERTA DAMPAK POSITIFNYA PADA KETERAMPILAN KOGNITIF PEMAIN - Hafizh As Shoqri; Cindy Taurusta; Sumarno Sumarno (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
Parkour 3D games have gained popularity and attracted the interest of players and game developers. These games not only serve as entertainment but also have the potential to enhance cognitive skills such as speed, agility in thinking, and decision-making. However, there is a lack of focus on the relationship between 3D parkour games and the enhancement of speed, agility in thinking, and decision-making. This study aims to explore the impact of playing parkour 3D games on speed, agility in thinking, and decision-making, providing insights into the role of games in developing cognitive and motor skills and the contribution of technology in improving quality of life. The research findings from questionnaires and game analysis indicate that playing parkour 3D games has significantly improved players' speed of thinking, agility, decision-making skills, focus, and concentration, leading to the conclusion that the design of 3D parkour games has been successful in enhancing cognitive skills.